The role of bank credit in alleviating the housing problem in Iraq for the period (2004-2021) - Kazar, Yasier Neamah; Hassan, Kareem Obayes (Edelweiss Applied Science and Technology, 2024)
It is no secret that bank credit plays an effective role in the economic and social life of all societies, especially in terms of stability and prosperity through the necessary financing for investors and individuals seeking their needs for housing units. The research was based on the financing provided by the relevant authorities in Iraq, such as the Real Estate Bank and the Housing Fund, with the support of the Central Bank through its well-known initiatives. The importance of the research lies in the ability of banks and relevant authorities to provide an appropriate climate for those concerned with the housing problem and meet their need to reduce this problem as much as possible if the required capital is available.As for the aim of the research, it revolves around the extent to which bank credit has an impact on reducing and effectively influencing the housing problem in Iraq. The research concluded that credit is linked to the housing problem through the existence of an inverse relationship between the housing problem as a dependent variable and bank credit directed to the housing sector, whether cash or pledged, as independent variables.The researcher reached important recommendations for a solution, the most prominent of which is the necessity for the state to adopt a new strategy to eliminate the housing crisis, which includes a specific and well-studied timetable to come up with unconventional solutions and not be satisfied with patchwork solutions and policies. The role of the private sector must also be activated in investing in the housing sector and providing all types of support and incentives to it, in addition to working to increase investment financial allocations directed to the housing sector. From the federal budget in order to meet as much as possible the need for housing units to alleviate the housing crisis, not to mention reviewing the laws and legislation related to the housing sector in a way that leads to making the housing sector an attractive sector for investment to attract the necessary capital for it.